Comparison of Robotic-Assisted vs. Conventional Laparoscopy for Para-aortic Lymphadenectomy in Gynecological Malignancies: A Systematic Review and Meta-Analysis - Zhou, Zhengli; Ge, Jing; Ye, Kefan; Zhang, Yifeng; Hu, Qian; Wang, Limei; Chen, Yiwen (Frontiers in Surgery, 2023)
Background Robotic-assisted surgery is one of the novel minimally invasive surgical techniques for the treatment of gynecological malignancies. The aim of this systematic review and meta-analysis was to compare the outcomes of robot-assisted vs. conventional laparoscopy for para-aortic lymphadenectomy (PAL) in patients with gynecological malignancies. Methods An electronic search in PubMed, Scopus, Cochrane Central Register of Controlled Trials (CENTRAL), and Google Scholar databases was performed for articles, published up to 01st November 2021. Outcomes including operating time (OT), total blood loss (TBL), length of stay (LOS), and complication rate (CR) in robot-assisted vs. conventional laparoscopy were investigated. Results A total of nine studies (7 non-RCTs and 2 RCTs) involving 914 participants were included. Of them, 332 patients underwent robotic laparoscopy (robotic group) and 582-conventional laparoscopy (conventional laparoscopy group). A significant decrease in TBL (MD = −149.1; 95% CI: −218.4 to −79.91) [ml] was observed in the robotic group as compared to the conventional laparoscopy group. However, no significant difference was noted for OT, CR, and LOS in the overall findings. Further subgroup analysis showed that the robotic group had a lower OT in mixed histological populations and studies reporting on the extraperitoneal approach. The lower chance of TBL was observed in mixed histological populations and studies involving extraperitoneal approach, Caucasian population, and non-RCTs design. Conclusions Robotic laparoscopy has a significant advantage over the conventional laparoscopy approach for PAL in gynecological malignancies. Further prospective observational studies embedded with a large sample size are needed to validate our findings.